Approaches to modulate buffalo gut microbiome for efficient feed utilization and reduced environmental pollution - Vijit Dey; Puran C. Lailer; Tirtha K. Datta (Revista Científica)
Buffaloes are excellent converters of highly fibrous feeds into edible products like milk and meat due to the rumen microbiome structure and their functionality. About 37– 44% of global methane emissions, mainly due to enteric fermentation of feeds by fibrolytic bacteria and formation of methane by methanogenic archaea, present in the rumen, is contributed by ruminants and a major source of methane production in the agriculture sector. Though the hyper ammonia-producing bacteria (HAB) are present inside the rumen (Clostridium aminophilum, Peptostreptococcus anaerobius, and Clostridium sticklandii) in low numbers, the concentration of ammonia (>300 nmol NH3/ mg cell protein/ min) they can produce makes them quantitatively important. Methane is the second major greenhouse gas contributing to climate change. At the same time, ammonia is a potent environmental pollutant and is liable for the depletion of oxygen in the body water, reduction of soil pH, and generation of harmful aerosol fine particles accompanied by the augmented menace of pulmonary diseases. Therefore, the roles played by the microbes in the rumen microbial ecosystem are fundamental to developing innovative methods to modulate the rumen microbiome to improve buffalo production while reducing environmental impact. The major fiber-degrading bacteria in buffalo rumen are Fibrobacter succinogenes, Ruminococcus flavefaciens, R. albus, Prevotella ruminicola, and Butyrivibrio fibrisolvens. However, our recent studies with metagenomic analysis of rumen methanogens showed that Methanobrevibacter was the predominant genus for cattle and buffalo. At the same time, Methanomicrobium is much higher in buffaloes than cattle (18% vs. 4.5%). Methanomassiliicoccaceae methanogens, a major methylotrophic group of archaea, was isolated in the rumen of buffaloes for the first time. Hyper ammonia- producing bacteria (HAB) are responsible for a faster rate of ammonia production from dietary protein degradation, resulting in wastage of feed protein and environmental pollution. 16S rRNA sequences of enrichment culture of buffalo rumen content revealed Proteo-bacteria (61.1 - 68.2%) as most predominant bacteria followed by Unclassified bacteria (24-29%), Firmicutes (2.8-6.9%), Bacteriodetes (0.9-2%), Actinobacteria (0.1-1.1%), Fusobacteria (0.04-0.7%) and Synergistetes (0.1-0.4%) at phylum level. At the family and genus level, most of the sequences remained unclassified. Among sequences with valid family names, Acidaminococcaceae was most predominant, constituting 1.5 to 4.7% of sequences. Similarly, Acidaminococcus was most predominant at the genus level among sequences with valid genus names, constituting 1.4 to 4.1% of total bacterial sequences. Supplementation of bioactive compounds viz. essential oils (eugenol, origanum oil, thymol), saponins or tannins in pure form or through natural compounds (garlic oil, eucalyptus oil, clove oils, Sapindus mukorossi fruit, Glycyrrhiza glabra root, Ficus bengalensis leaves, Ficus glomerata leaves), which are rich in these bioactive were shown to reduce methane (30%) and ammonia production (50%) in buffaloes with improvement in body weight (14%), milk production (10%) and feed efficiency (15%) in Murrah buffaloes. A composite feed additive formulated to reduce the methanogenic archaeal population without affecting fibrolytic rumen microbes has been demonstrated to increase milk production, antioxidant status, and immunity with abatement of enteric methane production in Murrah buffaloes. Strategic supplementation of Moringa leaves or feeding of low lignin sorghum cultivars were demonstrated to enhance feed utilization and production performances of Murrah buffalo with reduction of enteric methane production. Therefore, insight study of buffalo rumen microbiome and dietary interventions through strategic feeding and development of new products for rumen stimulants, anti-methanogenic compounds, or alternate hydrogen sinks in the rumen could be the promising strategies for modulating gut health for efficient conversion of human inedible feeds to edible animal products so reducing the impact of buffalo production on environmental pollution.